The Relationship Between Father's Attachment And Self-Disclosure In Adolescent Girls - Nurul Muchlisah; Sitti Murdiana (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Adolescence is a transitional phase from childhood to adulthood. Adolescents experience complex problems not only because of internal influences within themselves, but also from the influence of opportunities and support from adults, in this case parents. Fathers play a very important role in building a child's role in their environment and in determining the child's attachment status. By forming a good attachment between father and child, it is possible for teenage girls to be able to carry out self-disclosure. This study aims to determine the relationship between father attachment and self-disclosure in adolescent girls. The sample in this study consisted of 292 subjects aged 15-22 years. Data collection was carried out using a Likert scale, namely attachment scale and self-disclosure scales. Test the hypothesis using Spearman Rho correlation analysis with the help of SPSS 24. The results show that There is a significant relationship between father attachment and self-disclosure in adolescent girls, with a significance value of 0.000 <0.05. This means that the higher the attachment, the higher the self-disclosure in adolescent girls. The implications of this research are that it can be a reference for teenagers about the importance of attachment and making efforts to increase attachment.